Macromolecular crowding and decellularization method increase the growth factor binding potential of cell-secreted extracellular matrices - Fok, Shierly W.; Gresham, Robert C. H.; Ryan, Weston; Osipov, Benjamin; Bahney, Chelsea; Leach, J. Kent (Frontiers in Bioengineering and Biotechnology, 2023)
Recombinant growth factors are used in tissue engineering to stimulate cell proliferation, migration, and differentiation. Conventional methods of growth factor delivery for therapeutic applications employ large amounts of these bioactive cues. Effective, localized growth factor release is essential to reduce the required dose and potential deleterious effects. The endogenous extracellular matrix (ECM) sequesters native growth factors through its negatively charged sulfated glycosaminoglycans. Mesenchymal stromal cells secrete an instructive ECM that can be tuned by varying culture and decellularization methods. In this study, MSC-secreted ECM was modified using λ-carrageenan as a macromolecular crowding (MMC) agent and decellularized with DNase as an alternative to previous decellularized ECMs (dECM) to improve growth factor retention. MMC dECM contained 7.7-fold more sulfated glycosaminoglycans and 11.7-fold more total protein than dECM, while there was no significant difference in residual DNA. Endogenous BMP-2 was retained in MMC dECM, whereas BMP-2 was not detected in other ECMs. When implanted in a murine muscle pouch, we observed increased mineralized tissue formation with BMP-2-adsorbed MMC dECM in vivo compared to conventional dECM. This study demonstrates the importance of decellularization method to retain endogenous sulfated glycosaminoglycans in dECM and highlights the utility of MMC to upregulate sulfated glycosaminoglycan content. This platform has the potential to aid in the delivery of lower doses of BMP-2 or other heparin-binding growth factors in a tunable manner.